Design of Variable Structure Control System With Nonlinear Time-Varying Sliding Sector - Yaodong Pan; Kumar, K.D.; Guangjun Liu; Furuta, K. (IEEE transactions on automatic control, 2009)
A variable structure control (VSC) algorithm is proposed with a nonlinear time-varying (NTV) sliding sector for a class of nonlinear time-variant systems represented in a state-dependent linear time-variant form. The NTV sliding sector, a subset of the state space is designed by the state-dependent differential Riccati equation (SDDRE). A VSC law is designed such that the system enters the sliding sector in finite time and a Lyapunov function candidate decreases inside the NTV sliding sector. An NTV control and a sliding mode control algorithms are proposed based on the solution of the SDDRE as well.